Labour force activity after 65: what explain recent trends in Denmark, Germany and Sweden? - Mona Larsen; Peder J Pedersen (Journal for Labour Market Research, 2017)
In most OECD member countries labour force attachment, has increased in recent years not only in the age groups 60-64 years but also among people 65 years and older. Focus in this paper is on the trend in older workers' labour force participation in Denmark, Germany and Sweden since 2004. Main emphasis is given to people aged 65-69 years eligible for social security retirement programs from age 65. The gender aspect is included to accommodate different trends for women and men. To explain country differences in trends, the importance of changes in retirement policies of relevance for this age group and cohort relevant changes in education and health is examined and discussed. Further, country differences in the impact from education and health is examined. Results show that the largest increase in labour force participation among people aged 65-69 years has taken place in Sweden following by Germany, while the increase in Denmark is rather small. While the increase in Germany mainly seems to be a result of policy reforms, the increase in Sweden appear to be a result of a combination of policy changes and an increasing educational level. Financial incentives seem most important in Germany and only of minor importance in Denmark, where policy changes directed towards individuals above the age of 65 appear to have been too small so far to affect retirement behaviour significantly. – – In den meisten OECD-Mitgliedsländern ist in den letzten Jahren nicht nur die Beschäftigung in der Altersgruppe der 60-64-jährigen, sondern auch bei Personen ab 65 Jahren gestiegen. Dieser Artikel analysiert die Arbeitsmarktbeteiligung Älterer in Dänemark, Deutschland und Schweden seit 2004. Das Hauptaugenmerkt liegt dabei auf Menschen in der Altersgruppe der 65 bis 69-jährigen. Geschlechtsspezifische Unterschiede werden berücksichtigt, um unterschiedliche Entwicklungen für Frauen und Männer erfassen zu können. Um länderspezifische Unterschiede erklären zu können, werden wichtige Veränderungen in den Rentenprogrammen, die für diese Altersgruppe relevant sind, sowie Änderungen im Bildungsniveau und Gesundheitszustand dieser Alterskohorte untersucht und diskutiert. Weiterhin werden länderspezifische Unterschiede beim Einfluss von Bildung und Gesundheit untersucht. Die Ergebnisse zeigen, dass die größte Steigerung der Arbeitsmarktteilnahme unter den 65 bis 69-jährigen in Schweden stattgefunden hat, gefolgt von Deutschland, während die Steigerung in Dänemark eher gering ausfällt. Während der Anstieg in Deutschland vor allem ein Ergebnis politischer Reformen zu sein scheint, ist der Anstieg in Schweden auf eine Kombination aus politischen Reformen und einem gestiegenen Bildungsniveau zurückzuführen. Finanzielle Anreize scheinen in Deutschland den größten Einfluss gehabt zu haben. Demgegenüber waren die Rentenänderungen für über 65-jährige in Dänemark zu gering, um deren Arbeitsmarktbeteiligung signifikant zu beeinflussen.
Keywords: I15; I25; J14; J26; 330; Employment; Older workers; Program changes; Education; Health